A Review of Molecular Responses of Catfish to Bacterial Diseases and Abiotic Stresses - Zhou, Tao; Yuan, Zihao; Tan, Suxu; Jin, Yulin; Yang, Yujia; Shi, Huitong; Wang, Wenwen; Niu, Donghong; Gao, Lei; Jiang, Wansheng; Gao, Dongya; Liu, Zhanjiang (Frontiers in Physiology, 2018)
Catfish is one of the major aquaculture species in the US. However, the catfish industry is threatened by several bacterial diseases such as enteric septicemia of catfish (ESC), columnaris disease and Aeromonas disease, as well as by abiotic stresses such as high temperature and low oxygen. Research has been conducted for several decades to understand the host responses to these diseases and abiotic stresses. With the development of sequencing technologies, and the application of genome-wide association studies in aquaculture species, significant progress has been made. This review article summarizes recent progress in understanding the molecular responses of catfish after bacterial infection and stress challenges, and in understanding of genomic and genetic basis for disease resistance and stress tolerance.